Effect of calcination temperature on the structural, dielectric and optical properties of nano-sized M-type barium hexaferrites. (2019) - Tekou Carol T, Tchouank; Mohammed, J.; Srivastava, A.K.
Abstract: M-type hexagonal ferrites have found considerable application in electronics industry as a result of tuning the electrical, dielectric and magnetic properties to match with the intended application. M-type hexagonal ferrites with improved dielectric properties are useful in high frequency application. In this research, we studied the effect of heat treatment in M-type barium hexagonal ferrites with chemical composition Ba1- x Al x Fe12- y Mn y O19 ( x =0.6 and y =0.3) synthesized by sol-gel auto-combustion method. The prepared sample was sintered at four different temperatures (T= 750°C, 850°C, 950°C and 1050°C). The synthesized samples were characterized using X-ray diffraction (XRD), field electron scanning electron microscopy (FESEM), impedance analyser and UV-Vis spectroscopy. The band gap of the prepared sample is obtained from UV-Vis spectroscopy data. The dielectric properties were explained on the basis of Koop's phenomenological theory and Maxwell Wagner model. The prepared sample exhibit high dielectric constant at low frequency which is typical of a ferrite material. The sample calcined at and 750°C has the highest dielectric constant at high and low frequency. Lowest dielectric loss at high frequency is observed in the sample calcinated at 1050°C while that calcinated at 850°C show the lowest loss at high frequency.